Ability of anaerobic digestion to remove antibiotics contained in swine manure. (December 2021) - Yin, Fubin; Dong, Hongmin; Zhang, Wanqin; Wang, Shunli; Shang, Bin; Zhu, Zhiping
Abstract : Antibiotics in animal manure, which are used to treat animal diseases, have become a major concern due to human and ecological health risks. Anaerobic digestion (AD) is viable for treating manure because it generates energy. However, the ability of AD to completely eliminate antibiotics remains unclear. Therefore, the AD ability of swine manure containing 10 antibiotics was investigated. The results showed that the thresholds of complete antibiotic reduction were 25, 50, 50, 75, 75, and 75 mg (kg TS) −1 for SD, CIP, SQ, SAR, DIF, and SA, respectively. At their thresholds, SD, CIP, and SA could increase methane production, but the opposite results were obtained for SQ, SAR, and DIF. The modified Gompertz model showed good application for AD with different antibiotic loads. Antibiotic reduction and methane production are strongly correlated for the antibiotics of SAR and ENR, so their reduction performance can be inferred simply by determining their methane production. Graphical abstract: Image 1 Highlights: Thresholds of antibiotic complete reduction were got in anaerobic digestion (AD). Antibiotics with their threshold may increase or decrease methane production of AD. The modified Gompertz model can be applied for AD with different antibiotics. Relationship of antibiotic reduction and methane yield are relevant for SAR and ENR. Reduction rate of SAR and ENR can be indicated by their effect on methane yield.